Feasibility and Safety of Outpatient Thyroidectomy: A Narrative Scoping Review - Philteos, Justine; Baran, Elif; Noel, Christopher W.; Pasternak, Jesse D.; Higgins, Kevin M.; Freeman, Jeremy L.; Chiodo, Albino; Eskander, Antoine (Frontiers in Endocrinology, 2021)
Background: Outpatient thyroid surgery is gaining popularity as it can reduce length of hospital stay, decrease costs of care, and increase patient satisfaction. There remains a significant variation in the use of this practice including a perceived knowledge gap with regards to the safety of outpatient thyroidectomies and how to go about implementing standardized institutional protocols to ensure safe same-day discharge. This review summarizes the information available on the subject based on existing published studies and guidelines. Methods: This is a scoping review of the literature focused on the safety, efficacy and patient satisfaction associated with outpatient thyroidectomies. The review also summarizes and editorializes the most recent American Thyroid Association guidelines. Results: In total, 11 studies were included in the analysis: 6 studies were retrospective analyses, 3 were retrospective reviews of prospective data, and 2 were prospective studies. The relative contraindications to outpatient thyroidectomy have been highlighted, including: complex medical conditions, anticipated difficult surgical dissection, patients on anticoagulation, lack of home support, and patient anxiety toward an outpatient procedure. Utilizing these identified features, an outpatient protocol has been proposed. Conclusion: The salient features regarding patient safety and selection criteria and how to develop a protocol implementing ambulatory thyroidectomies have been identified and reviewed. In conclusion, outpatient thyroidectomy is safe, associated with high patient satisfaction and decreased health costs when rigorous institutional protocols are established and implemented. Successful outpatient thyroidectomies require standardized preoperative selection, clear discharge criteria and instructions, and interprofessional collaboration between the surgeon, anesthetist and same-day nursing staff.